The Comparative Analysis of Asthma Treatment in Pediatric Patients of Russia and China - Yue Li (Journal of Global Pharma Technology, 2020)
The correctly prescribed treatment regimen plays a key role in a successful control of asthma symptoms. Therefore, the monitoring studies aimed to facilitate rational medicine use for asthma treatment are relevant. The analysis of drug prescription patterns for asthma in pediatric outpatient care of Russia and China, as well as evaluation of the prescribed therapy conformity with the modern international standards on asthma treatment. This is a retrospective pharmacoepidemiological study on medical histories of asthma patients under the age of 18. The study involved 720 children’s medical records (327 Russian and 393 Chinese) and prescribed medications for asthma within the period of 2018. The short-acting beta-2-agonists in Russia and China were typically prescribed as quick-relief drugs for treating asthma attacks in pediatric patients (in 78.6% and 83.7% of cases, respectively (p> 0.05)). Inhaled corticosteroids (in 65.1% of cases) and leukotriene receptor antagonists (in 18.6% of children) were most frequently prescribed for a long-term control of asthma symptoms in China. In Russia, the rate of commonly prescribed long-term relievers ranged as follows: inhaled corticosteroids -54.1%, cromones-19.6%, inhaled corticosteroids in combination with long-acting beta-2-agonists -15.4%. The drug prescribing patterns for bronchial asthma management in pediatric patients of Russia and China conformed to the modern treatment standards. Still, some differences in asthma therapy (relatively short anti-inflammatory therapy courses, unreasonably prescribed cromons in Russia) were found, which required deeper pharmacoepidemiological monitoring in that field. Keywords: Commonly prescribed asthma medications in pediatric patients, Mistakes in pediatric asthma management, Asthma medication prescribing in China and Russia.